Research and Community Service Performance during the COVID-19 Pandemic and Their Performance Management Response (Study in a Public University) - Nuh, Mohammad (Brawijaya University, 2024)
The Covid-19 pandemic influenced various aspects of lives, such as in health, economy, and education sector. The conditions of these sectors attracted academics and practitioners, who in turn conducted research during the pandemic period. One interesting and rarely discussed aspect is the impact of the Covid-19 pandemic on the process and performance of university research and community service. This study aimed to evaluate the impact of the Covid-19 pandemic on the process and performance of research and community service. This research was conducted at Brawijaya University using pragmatic evaluation methods and a survey research approach. The unit of analysis was institutions/units related to research and community service activities, for instance, BPPM, Study Centre, Research Groups, and Laboratories. The researcher distributed questionnaire through google form. Although only 52 people responded to the questionnaire, they represented each institution as the unit of analysis in this research. The research findings showed most of the respondents conveyed that Covid-19 pandemic had impact on the process and performance of the research and community services. As suggestion, research and community service management are required to make improvement and adjustment to ensure continuous process and performance.